2005
DOI: 10.1016/j.vaccine.2005.02.026
|View full text |Cite
|
Sign up to set email alerts
|

A vector expressing feline mature IL-18 fused to IL-1β antagonist protein signal sequence is an effective adjuvant to a DNA vaccine for feline leukaemia virus

Abstract: DNA vaccination using vectors expressing the gag/pol and env genes of feline leukaemia virus (FeLV) and plasmids encoding feline interleukin-12 (IL-12) and IL-18 completely protected cats from viraemia following challenge [Hanlon L, Argyle D, Bain D, Nicolson L, Dunham S, Golder MC, et al. Feline leukaemia virus DNA vaccine efficacy is enhanced by coadministration with interleukin-12 (IL-12) and IL-18 expression vectors. J Virol 2001;75:8424-33]. However, the relative contribution of each cytokine gene towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Innate immunity probably plays an important role, as suggested by abortive infections in naive cats and some in vitro studies (21). In vaccinated cats, several studies have shown that protection against persistent antigenemia can be obtained in the absence of neutralizing antibodies (22)(23)(24), suggesting a key role for vaccine-induced cellmediated immune responses (25). However, like other retroviruses, FeLV has developed mechanisms to interfere with the host immune response and establish persistent infection.…”
mentioning
confidence: 99%
“…Innate immunity probably plays an important role, as suggested by abortive infections in naive cats and some in vitro studies (21). In vaccinated cats, several studies have shown that protection against persistent antigenemia can be obtained in the absence of neutralizing antibodies (22)(23)(24), suggesting a key role for vaccine-induced cellmediated immune responses (25). However, like other retroviruses, FeLV has developed mechanisms to interfere with the host immune response and establish persistent infection.…”
mentioning
confidence: 99%
“…However, it has recently been reported that IL-18 also augments the IFN-γ-inducing capacity of vaccines, independently of IL-12 [ 42 ]. IL-18 has also been tested as a vaccine adjuvant, and enhanced the efficiencies of various vaccines in mammals [ 43 46 ]. Recently, we generated a rCDV that secretes bioactive canine IL-18 and induces IFN-γ production by canine peripheral blood mononuclear cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, they have practical potential as carrier molecules, having shown less toxicity in both experimental animals and human immunization (29)(30)(31). Research has also shown that co-administration of cytokine proteins or cytokine gene-encoded plasmids enhances comprehensive humoral and cellular immune responses (32)(33)(34)(35). Recently, synthetic CpGs, which prime a Th1 immune response and have shown some encouraging results in H. pylori vaccines, have been approved for use as adjuvants in humans (21,23,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%